1993
DOI: 10.1111/j.1346-8138.1993.tb01296.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Elevated Serum Squamous Cell Carcinoma (SCC)‐Related Antigen and Lactate Dehydrogenase (LDH) Levels in Senile Erythroderma Following Eczema

Abstract: Clinical and laboratory tests were used to evaluate fourteen patients with senile erythroderma following eczema, and the results were compared with those from four patients with psoriatic erythroderma, two with Sézary syndrome, and twelve with prurigo chronica multiformis or nummular dermatitis. Characteristic laboratory findings included elevated serum squamous cell carcinoma-related antigens (SCC-RAg), high lactate dehydrogenase (LDH), peripheral-blood eosinophilia, and a decreased peripheral blood lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Levels of these complexes may be related to disease activity, and measurement may provide a tool for monitoring therapeutic result. Increased levels of complexes between elastase and inhibitors, but also of fi-ee elastase or free inhibitor, have been reported in lung cancer [30], neonatal systetnic infection [31,32], adult respiratory distress syndrome [27,32], cervical cancer [33,34], psoriasis, eczema, and other cutaneous disor- ders [35][36][37], and these levels can be used as parameters for monotoring disease activity. In normal epidermis, anti-elastase activity is hardly detectable [1], although the presence of al-PI and a2 macroglobulin in normal skin has been described [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of these complexes may be related to disease activity, and measurement may provide a tool for monitoring therapeutic result. Increased levels of complexes between elastase and inhibitors, but also of fi-ee elastase or free inhibitor, have been reported in lung cancer [30], neonatal systetnic infection [31,32], adult respiratory distress syndrome [27,32], cervical cancer [33,34], psoriasis, eczema, and other cutaneous disor- ders [35][36][37], and these levels can be used as parameters for monotoring disease activity. In normal epidermis, anti-elastase activity is hardly detectable [1], although the presence of al-PI and a2 macroglobulin in normal skin has been described [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…His history indicated occasional erythematous lesions on the body surface from about one year before. On admission, laboratory data showed high LDH 980 IU/L [as one erythroderma marker (3)], AST (GOT), 22 IU/L, AL (GPT), 18 IU/L, 18% eosinophilia and 280 IU/ml IgE. There had previously been allergic reaction subsequent to dried saury fish ingestion and, possibly, there were other causes.…”
Section: Case Reportmentioning
confidence: 99%
“…Furthermore, positive immunohistochemical staining for SCCr-Ag monoclonal antibody was detected in the skin biopsy of the same patients (17). The signi¢cance of this ¢nding remains controversial; it has been suggested that SCCr-Ag may be a marker of erythroderma (15) or may be related to serine proteinase activation occurring in psoriasis (16). In this study we investigated serum levels of SCCr-Ag in a group of psoriatic nonerythrodermic patients in the acute and remission phases of the disease in order to verify whether SCCr-Ag is a useful marker of disease activity and whether there is any correlation with other immunological parameters.…”
mentioning
confidence: 97%
“…We have demonstrated that the levels of circulating ICAM-1z lymphocytes correlate with cutaneous involvement, while persistence of some cellular and soluble immunological activation markers was observed in apparently normal skin (12,13). Recently, some authors have reported high serum levels of squamous cell carcinoma related antigen (SCCr-Ag), a neoplastic marker speci¢cally raised in squamous cell carcinoma of the cervix, lung and oesophagus (14), in dermatological diseases such as senile erythroderma following eczema (15) and psoriasis (16). Furthermore, positive immunohistochemical staining for SCCr-Ag monoclonal antibody was detected in the skin biopsy of the same patients (17).…”
mentioning
confidence: 98%